Survey on physical fitness levels of athletes aged 13-15 years old at Satria Mandiri Soccer School, Bojonegoro Regency - Arjuna Arya Nugraha; Moch. Yunus; Prisca Widiawati (Journal of Science and Education (JSE), 2022)
Physical fitness is one of the important components in the sport of football, because the game of football is played within 2x45 minutes so that a valid fitness status is needed in order to play football optimally. This study was conducted to determine the status of physical freshness in athletes aged 13 to 15 years at SSB Satria Mandiri, Bojonegoro Regency. The method in this study is descriptive quantitative with survey techniques. The population and samples used were athletes aged 13 to 15 years at the Satria Mandiri football school which totaled 22 athletes. Data collection includes several tests, a 50-meter running test using a running track, a body lift hanging test using poles/bars, a 60-second seating test, an upright jumping test using a board, a 1000-meter running test using a running track. Data analysis in this study is quantitative descriptive statistics. The results of this study obtained that of the 22 athletes who were subjects, 12 athletes obtained the moderate category with a percentage of 54.54%. The conclusion obtained from this study is that the level of physical freshness in athletes aged 13-15 years at the Satria Mandiri football school as a whole shows a moderate category.